On-chip fabrication and in-flow 3D-printing of microgel constructs: from chip to scaffold materials in one integral process - Reineke, Benjamin; Paulus, Ilona; Löffelsend, Sophia; Yu, Chien Hsin; Vinogradov, Dmitrii; Meyer, Anna; Hazur, Jonas; Röder, Jonas; Vollmer, Madita; Tamgüney, Gültekin; Hauschild, Stephan; Boccaccini, Aldo R.; et al. (Biofabrication, 2024)
Bioprinting has evolved into a thriving technology for the fabrication of cell-laden scaffolds. Bioinks are the most critical component for bioprinting. Recently, microgels have been introduced as a very promising bioink, enabling cell protection and the control of the cellular microenvironment. However, the fabrication of the bioinks involves the microfluidic production of the microgels, with a subsequent multistep process to obtain the bioink, which so far has limited its application potential. Here we introduce a direct coupling of microfluidics and 3D-printing for the continuous microfluidic production of microgels with direct in-flow printing into stable scaffolds. The 3D-channel design of the microfluidic chip provides access to different hydrodynamic microdroplet formation regimes to cover a broad range of droplet and microgel diameters. After exiting a microtubing the produced microgels are hydrodynamically jammed into thin microgel filaments for direct 3D-printing into two- and three-dimensional scaffolds. The methodology enables the continuous on-chip encapsulation of cells into monodisperse microdroplets with subsequent in-flow cross-linking to produce cell-laden microgels. The method is demonstrated for different cross-linking methods and cell lines. This advancement will enable a direct coupling of microfluidics and 3D-bioprinting for scaffold fabrication.
CRIS-Team Scopus Importer:2024-04-05
Keywords: 3D-printing; microfluidics; microgels